Study on energy conversion characteristics and pressure fluctuation interference characteristics between two stage impellers of the pump as turbine. (June 2023) - Li, Xiaolong; Lu, Yonggang; Shi, Weidong; An, Ce; Zhang, Zequan; Zhao, Yun
The process pump as turbine (PPAT) is an important infrastructure in chemical and oil refining process. When it operates in pump mode, it can provide high-pressure energy for chemical and oil refining system, and when it operates in turbine mode, it can recover the high-pressure energy from the oil medium. The operation stability of PPAT directly affects the normal operation and production of chemical and oil refining process. In this paper, the velocity slip characteristics of the PPAT in turbine mode and pump mode were studied, and the unsteady operation characteristics and the energy conversion and distribution mechanism of the first-stage impeller and second-stage impeller in pump mode were mainly studied, the pulsation amplitude frequency characteristics and induction mechanism of flow passage components under different flow conditions in pump mode are analyzed. The results show that PPAT has an efficiency peak in both pump mode and turbine mode, and the efficiency zone is significantly wider and the velocity slip loss is smaller in turbine mode; In turbine mode, with the increase of flow, the velocity slip loss of the first-stage impeller is larger than that of the second-stage impeller; In the pump mode, the velocity slip loss of the first-stage impeller is greater under the conditions of minimum flow and maximum flow, the pressure fluctuation in the PPAT is mainly distributed in the first stage diffuser and the second stage diffuser. The main factor causing the pressure fluctuation in the PPAT is the dynamic and static interference effect between the first-stage impeller and the first-stage diffuser.